2022
DOI: 10.3390/vaccines10030469
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of BNT162b2 and mRNA-1273 Vaccines against COVID-19 Infection: A Meta-Analysis of Test-Negative Design Studies

Abstract: Although numerous COVID-19 vaccines are effective against COVID-19 infection and variants of concern (VOC) in the real world, it is imperative to obtain evidence of the corresponding vaccine effectiveness (VE). This study estimates the real-world effectiveness of the BNT162b2 and mRNA-1273 vaccines against COVID-19 infection and determines the influence of different virus variants on VE by using test-negative design (TND) studies. We systematically searched for published articles on the efficacy of BNT162b2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The vulnerable population, particularly those unvaccinated or with coexisting underlying diseases, represents an unprecedented challenge in addressing Omicron spread ( 102 ). Several studies have confirmed that COVID-19 vaccines remain an effective protective measure in interrupting Omicron transmission; simultaneously, the mRNA vaccines, notably homologous or heterologous boosters, are worthy candidates for priority consideration ( 42 , 100 , 102 106 ). There was limited or no data on VE against various variants, including Omicron, in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…The vulnerable population, particularly those unvaccinated or with coexisting underlying diseases, represents an unprecedented challenge in addressing Omicron spread ( 102 ). Several studies have confirmed that COVID-19 vaccines remain an effective protective measure in interrupting Omicron transmission; simultaneously, the mRNA vaccines, notably homologous or heterologous boosters, are worthy candidates for priority consideration ( 42 , 100 , 102 106 ). There was limited or no data on VE against various variants, including Omicron, in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Some research suggests vaccine effectiveness might be higher with mRNA‐1273 compared to BNT162b2. 35 , 36 Sixth, we may have missed some SARS‐CoV‐2 infections that were captured using rapid antigen tests. However, this number is likely low with widespread access to PCR testing during the study period, the administration of confirmatory PCR tests at Ontario transplant centers, and PCR testing upon admission to the hospital (regardless of the reason for admission).…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we did not have the power to present vaccine effectiveness estimates by vaccine type (e.g., BNT162b2 versus mRNA‐1273) or by solid organ transplant type (e.g., lung versus kidney). Some research suggests vaccine effectiveness might be higher with mRNA‐1273 compared to BNT162b2 35,36 . Sixth, we may have missed some SARS‐CoV‐2 infections that were captured using rapid antigen tests.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world data revealed for the mRNA vaccines (mRNA-1273 and BNT162b2) a very high vaccine effectiveness of more than 90% with respect to the prevention of COVID-19 [ 14 , 15 ]. Later on, data from Israel and from New York showed that there is a waning of the immunity [ 3 , 16 ].…”
Section: Discussionmentioning
confidence: 99%